(untitled) (Construction Economics and Building, 2021)
Corporate Social Responsibility (CSR) is one of the best strategies that companies used in minimising negative societal and environmental impacts, enhancing economic development and improving social progress concurrently. However, there are many factors discouraging construction companies to implement or establish a CSR plan. Furthermore, there are few empirical studies in relation to CSR in construction, and the majority of empirical research on CSR implementation are rooted in the organisational and economic context of the developed world. Therefore, the current study seeks to investigate the factors inhibiting CSR initiatives among construction companies within the context of a developing country such as Nigeria. The study adopted a survey research method. Questionnaires were administered to a purposively selected group of managing directors, directors, other top construction professionals or management personnel involved in the operation of small, medium and large construction companies in Nigeria. A total of 196 questionnaires were administered among the sampled respondents out of which a total of 119 representing 61% were adequately filled and returned. The data collected were analysed using descriptive and inferential statistics. The results revealed corruption tendencies borne from lack of transparency between companies and government, lack of CSR benefits measurement, lack of financial resources, inadequate support from top management and lack of governmental support as the top five factors inhibiting CSR initiatives among construction companies in Nigeria. In addition, the results from the study revealed that, there is no statistically significant difference in factors inhibiting CSR in construction between indigenous and expatriate and partly indigenous/partly expatriate companies. The findings provide in-depth insight of the factors inhibiting CSR programmes in construction that can help top construction professionals and management personnel in construction companies facilitate development of strategies required to mitigate the factors inhibiting CSR programmes.